Digital poster usage on increasing parents' knowledge of dental and oral health maintenance - Nurrochman, Aditya; Putri, Rifa Fauziah Syaifia; Setya, Andi (Center of Excellent (Pusat Unggulan Iptek), 2025)
Background: tooth decay is a damage on teeth from email to dentin. Tooth decay will happen because less knowledge of every person and they need dental health education to improve their knowledge. To give education, it needs digital poster as a media. Digital poster have some aspects like illustration, typography, and color. That aspects can make digital poster more attractive. The goals of this research is to analyze dental health knowledge of parents before and after giving dental health education with digital poster. Research Method: socialization with pre and post design to 37 respondents. Results: data is normally distributed for both variables, namely the pre test of 0.033 0.05. There is a connection between pre test and post test because the pre test value is 63.38 < post test 81.08 and the value of Sig. 0 < 0.05. Conclusion: there is a impact from digital poster to improve dental health knowledge of parents in 03 Elemntary School East Cempaka Putih.